Pharmacokinetics of ketorolac in juvenile loggerhead sea turtles (Caretta caretta) after a single intramuscular injection. Issue 4 (18th February 2021) - Gregory, Taylor M.; Harms, Craig A.; Gorges, Melinda A.; Lewbart, Gregory A.; Papich, Mark G.
Abstract: Ketorolac is a non‐steroidal anti‐inflammatory drug administered as an analgesic in humans. It has analgesic effects comparable to opioids but without adverse effects such as respiratory depression or restrictions because of controlled drug status. We designed this study to examine the potential of ketorolac as an analgesic for sea turtle rehabilitative medicine. Our objective was to determine the pharmacokinetics of a single 0.25 mg/kg intramuscular dose of ketorolac in a population of 16 captive‐raised juvenile loggerhead sea turtles ( Caretta caretta ). A sparse sampling protocol was utilized, and blood samples were collected for 12 hours after administration of ketorolac. Samples were analyzed with high‐pressure liquid chromatography (HPLC), and a nonlinear mixed effects model (NLME) was used to determine parameters for the population. With these methods, we identified a long elimination half‐life (βT1/2  = 11.867 hr) but a low maximum concentration (CMAX  = 0.508 µg/mL) and concentrations were below the level proposed to be therapeutic in humans (EC50  = 0.1–0.3 μg/mL) for most of the collection period. We conclude that ketorolac may not be an appropriate long‐term analgesic for use in loggerhead sea turtles at this dose; however, it may have some benefit as a short‐term analgesic.